2016
DOI: 10.1073/pnas.1607079113
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3 regulates neuronal reprogramming of cells from postnatal and aging mice

Abstract: We and others have shown that embryonic and neonatal fibroblasts can be directly converted into induced neuronal (iN) cells with mature functional properties. Reprogramming of fibroblasts from adult and aged mice, however, has not yet been explored in detail. The ability to generate fully functional iN cells from aged organisms will be particularly important for in vitro modeling of diseases of old age. Here, we demonstrate production of functional iN cells from fibroblasts that were derived from mice close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Our analysis found that individuals with nonsynonymous variants in FOXO3 had lower HbF levels. FOXO3 is a transcription factor that has been shown to be essential for erythroid maturation in mouse models, 22,24 and it is an important regulator of glucose metabolism, 17,60,61 among other functions 14,[62][63][64][65][66] ; however, it has not previously been implicated in HbF regulation. Here, we presented functional studies supporting the hypothesis that FOXO3 is a partial positive regulator of HbF, likely along with other factors; knockdown of FOXO3 in HSPCs from normal individuals reduced g-globin expression and production without altering b-globin expression and production.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis found that individuals with nonsynonymous variants in FOXO3 had lower HbF levels. FOXO3 is a transcription factor that has been shown to be essential for erythroid maturation in mouse models, 22,24 and it is an important regulator of glucose metabolism, 17,60,61 among other functions 14,[62][63][64][65][66] ; however, it has not previously been implicated in HbF regulation. Here, we presented functional studies supporting the hypothesis that FOXO3 is a partial positive regulator of HbF, likely along with other factors; knockdown of FOXO3 in HSPCs from normal individuals reduced g-globin expression and production without altering b-globin expression and production.…”
Section: Discussionmentioning
confidence: 99%
“…GFP-tagged miNSCs or hiNSCs (1 × 10 5 ) were plated on the glial cell feeder with NSC medium in a well of 24-well plate. To optimize the differentiation procedure, 24 h before plating miNSCs or hiNSCs, 3 × 10 4 glial cells were plated as the feeder, which were dissociated from P0 C57BL/6J mouse brain as previous described 80 . After 24 h, the medium was replaced with neuronal differentiation medium 1 (N3 medium supplemented with 2% B27, 1% N2, 2 mM glutamax, and 1 × Pen/Strep), which was replaced with neuronal differentiation medium 2 [neurobasal-a medium supplemented with 1 × Insulin-transferrin-selenium solution (Thermo Fisher), 30 ng/ml BDNF, 30 ng/ml CNTF, 30 ng/ml Nerve growth factor (Pepro Tech), 10 μM forskolin, 25 mM l -glutamic acid, 200 mM l -glutamine, 1% B27, 1% N2, and 1 × Pen/Strep].…”
Section: Methodsmentioning
confidence: 99%
“…Further, in some iN studies, the age of the human donor has been negatively correlated with the percentage of iNs obtained [38], and fibroblasts from adult human donors are resistant to Ascl1/Brn2-based conversion, while fetal fibroblasts are highly amenable [38]. RE1-silencing complex (REST), a major neuronal gene repressor in non-neuronal cells, and the aging-associated TF FOXO3 play important roles in controlling neuronal gene expression and show differential activity between fetal and adult/old fibroblasts, resulting in decreased conversion efficacy in aged starting cells [38][39][40]. Again, the combination of the two pioneer factors Ascl1 and Ngn2, for example, fused via a 2A peptide sequence, has yielded iN efficiencies of typically over 50% across large sample sizes and does not appear to be affected by donor age [9,10,35].…”
Section: Enabling In Conversionmentioning
confidence: 99%